Analysis of the quality of life of the population older than the able-bodied age in Russia - N. Cheremisina; T. Cheremisina; Yu. Grishko (Вестник Северо-Кавказского федерального университета)
The purpose of this article is to analyze the quality of life of Russians older than working age in modern conditions based on official statistics. As a result of the study, Russia is assessed in international ratings on the quality of life of people of retirement age. The analysis of the life of Russian pensioners according to the main indicators of the international rating: healthcare, pension provision, quality of life, material well-being. In conclusion, disappointing conclusions are made: Russia's position on the quality of life of pensioners in international ratings can be assessed as unsatisfactory. Pension payments of Russian pensioners do not greatly exceed the established subsistence minimum; the pension is an insignificant part of the average salary in the country. It is difficult to characterize positively and material well-being. In addition, the level of health care, especially in rural areas, can not be assessed high enough.